Combining energy-based focal ablation and immune checkpoint inhibitors: preclinical research and clinical trials - Jiang, Minhan; Fiering, Steven; Shao, Qi (Frontiers in Oncology, 2023)
Energy-based focal therapy (FT) uses targeted, minimally invasive procedures to destroy tumors while preserving normal tissue and function. There is strong emerging interest in understanding how systemic immunity against the tumor can occur with cancer immunotherapy, most notably immune checkpoint inhibitors (ICI). The motivation for combining FT and ICI in cancer management relies on the synergy between the two different therapies: FT complements ICI by reducing tumor burden, increasing objective response rate, and reducing side effects of ICI; ICI supplements FT by reducing local recurrence, controlling distal metastases, and providing long-term protection. This combinatorial strategy has shown promising results in preclinical study (since 2004) and the clinical trials (since 2011). Understanding the synergy calls for understanding the physics and biology behind the two different therapies with distinctive mechanisms of action. In this review, we introduce different types of energy-based FT by covering the biophysics of tissue-energy interaction and present the immunomodulatory properties of FT. We discuss the basis of cancer immunotherapy with the emphasis on ICI. We examine the approaches researchers have been using and the results from both preclinical models and clinical trials from our exhaustive literature research. Finally, the challenges of the combinatory strategy and opportunities of future research is discussed extensively.